Response modification factors for reinforced concrete structures equipped with viscous damper devices - Abdi, Heshmatollah; Hejazi, Farzad; Jaafar, Mohd Saleh; Abd Karim, Izian (Budapest University of Technology and Economics, 2018)
The response modification factor is one of the seismic design parameters that determine the nonlinear performance of building structures during strong earthquakes. Most seismic design codes lead to reduced loads. Nevertheless, an extensive review of related literature indicates that the effect of viscous dampers on the response modification factor is no longer considered. In this study, the effect of implementing viscous damper devices in reinforced concrete structures on the response modification factor was investigated. Reinforced concrete structures with different stories were considered to evaluate the values of the response modification factors. A nonlinear statistic analysis was performed with finite element software. The values of the response modification factors were evaluated and formulated on the basis of three factors: strength, ductility, and redundancy. Results revealed that the response modification factors for reinforced concrete structures equipped with viscous damper devices are higher than those for structures without viscous damper devices. The number of damper devices and the height of buildings have significant effects on response modification factors. In view of the analytical results across different cases, we proposed an equation according to the values of damping coefficients to determine the response modification factors for reinforced concrete structures furnished with viscous damper devices.